2020
DOI: 10.1021/acssensors.9b01928
|View full text |Cite
|
Sign up to set email alerts
|

Improved Measurement of Proteins Using a Solid-State Nanopore Coupled with a Hydrogel

Abstract: Although resistive pulse sensing using solid-state nanopores is capable of single-molecule sensitivity, previous work has shown that nanoparticles, such as proteins, pass through nanopores too quickly for accurate detection with typical measurement apparatus. As a result, nanopore measurements of these particles significantly deviate from theoretically estimated current amplitudes and detection rates. Here, we show that a hydrogel placed on the distal side of a nanopore can increase the residence time of nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…We measured IgG in its native state using nanopores 23–31 nm in diameter and 15 nm long, backed with a poly­(ethylene glycol)-dimethacrylate (PEG-DMA) hydrogel of average mesh size ∼3.1 nm, as described previously (Figure S1). To determine the average event frequency ( f ), we divided the number of single-molecule events ( N ) by the duration of observation (Δ t ): f = N /Δ t . , We applied −50 mV to the nanopore and found that the event frequency rapidly increased following the protein addition and plateaued after 5–9 min (Figure S2), indicating the amount of time for protein monomers to homogeneously disperse throughout the measurement chamber.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We measured IgG in its native state using nanopores 23–31 nm in diameter and 15 nm long, backed with a poly­(ethylene glycol)-dimethacrylate (PEG-DMA) hydrogel of average mesh size ∼3.1 nm, as described previously (Figure S1). To determine the average event frequency ( f ), we divided the number of single-molecule events ( N ) by the duration of observation (Δ t ): f = N /Δ t . , We applied −50 mV to the nanopore and found that the event frequency rapidly increased following the protein addition and plateaued after 5–9 min (Figure S2), indicating the amount of time for protein monomers to homogeneously disperse throughout the measurement chamber.…”
Section: Resultsmentioning
confidence: 99%
“…As the neutral PEG-DMA hydrogel has an antifouling property and sterically interacts with translocating proteins, the size of the protein relative with respect to the mesh size of the hydrogel is an important factor to determine the efficiency of the hydrogel in facilitating a protein detection. We measured 400 pM poly- l -glutamic acid sodium salt (≤5.5 kDa), which has a hydrodynamic radius of 1.35 nm estimated from Equation S19, smaller than the 3.1 nm average mesh size of the PEG-DMA hydrogel . In the absence of a hydrogel, no events were detected over 45 min at −100 mV of applied voltage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the traditional techniques require a large number of identical protein samples, wherein it is challenging to record a singleprotein conformational change in a real-time manner (Ding et al, 2019). The nanopore-based approaches can achieve sensitive and label-free detection of a single protein even at extremely low concentrations as well as provide a dynamic view of protein conformation, confirming their ability for protein characterization (Acharya et al, 2020).…”
Section: Protein Detection and Sequencingmentioning
confidence: 98%
“…Fragment sizing, sequencing, and structure identification of biomolecules remain major objectives in the field of nanopore sensing. Likewise, the shape and size of NPs can be identified with these typical detection principles (Acharya et al, 2020;Si et al, 2020). For example, Karmi et al used Si 3 N 4 nanopores to detect gold NPs (AuNP) and differentiate the charged monomers (single particles) and dimers (two particles) based on their different translocation time through the pore (Figure 2J; Karmi et al, 2021).…”
Section: Nps Detection and Other Applicationsmentioning
confidence: 99%